WHAT IS YOUR FAVORITE MOVIE?: A STRATEGY OF ENGLISH EDUCATION STUDENTS TO IMPROVE ENGLISH VOCABULARY - Marta Widiawitasari Br Simamora; Lulud Oktaviani (Journal of English Language Teaching and Learning, 2020)
Vocabulary is one of the most important language components in learning the English language. A vocabulary is several English words that are taught to students in the teaching and learning process which goes hand in hand with all four English skills, especially listening. By increasing vocabulary, students’ ability for better understanding in listening, speaking, reading, and writing will likely increase. The more they listen, the more words they will add to their mastering vocabulary. Moreover, many kinds of media may be used to exercise students’ ability nowadays, which include music, video, movies, etc. English movies can provide a great chance for students to learn English vocabulary by listening. This could happen because in watching movies students often hear new words that they may never hear before. The instruments used were questionnaires and interviews. The result showed that by watching English Movie they could add some vocabularies to their memory through listening and watching the scene in the English Movie.